Complement-Mediated Microglial Phagocytosis and Pathological Changes in the Development and Degeneration of the Visual System - Borucki, Davis M.; Toutonji, Amer; Couch, Christine; Mallah, Khalil; Rohrer, Baerbel; Tomlinson, Stephen (Frontiers in Immunology, 2020)
Abstract The focus of this review is the role of complement-mediated phagocytosis in retinal and neurological diseases affecting the visual system. Complement activation products opsonize synaptic material on neurons for phagocytic removal, which is a normal physiological process during development, but a pathological process in several neurodegenerative diseases and conditions. We discuss the role of complement in the refinement and elimination of synapses in the retina and lateral geniculate nucleus, both during development and in disease states. How complement and aberrant phagocytosis promotes injury to the visual system is discussed primarily in the context of multiple sclerosis, where it has been extensively studied, although the role of complement in visual dysfunction in other diseases such as stroke and traumatic brain injury is also highlighted. Retinal diseases are also covered, with a focus on glaucoma and age-related macular degeneration. Finally, we discuss the potential of complement inhibitory strategies to treat diseases affecting the visual system.